Effects of the Laser Field on Dynamical Entanglement in Triatomic Molecules (Journal of Atomic and Molecular Sciences, 2018)
Algebraic approach to dynamical entanglement of triatomic molecules in laser fields are proposed. The effects of laser fields on dynamical entanglement are discussed. The researches show that the changes of two stretch vibrational entanglement along with the laser frequency are corresponding to vibrational transitions from different initial states to final states. The sustained entanglement will be implemented by using a two-step laser excitation.